Personal Branding Kang Dedi Mulyadi Gubernur Jawa Barat pada Kunjungan Desa Cirendeu - Amanda Nashita Putri; Valestina, Nabila Adrelya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Personal branding is not only relevant to businesses and individuals on social media but also constitutes a crucial strategy in the political sphere. Political figures who actively cultivate their personal branding through social media can positively impact society, particularly by enhancing access to political information. The personal branding approach of Kang Dedi Mulyadi (KDM) serves as a notable example. This study investigates the messages and meanings embedded in the YouTube channel